Maximising the wealth of few at the expense of the health of many: a public health analysis of market power and corporate wealth and income distribution in the global soft drink market - Benjamin Wood; Phil Baker; Gyorgy Scrinis; David McCoy; Owain Williams; Gary Sacks (BMC, 2021)
Abstract Background Many of the harms created by the global soft drink industry that directly influence human and planetary health are well documented. However, some of the ways in which the industry indirectly affects population health, via various socio-economic pathways, have received less attention. This paper aimed to analyse the extent to which market power and corporate wealth and income distribution in the global soft drink market negatively impact public health and health equity. In doing so, the paper sought to contribute to the development of a broad-based public health approach to market analysis. A range of dimensions (e.g., market concentration; financial performance; corporate wealth and income distribution) and indicators (e.g., Herfindahl Hirschman Index; earnings relative to the industry average; effective tax rates; and shareholder value ratios) were descriptively analysed. Empirical focus was placed on the two dominant global soft drink manufacturers. Results Coca-Cola Co, and, to a lesser extent, PepsiCo, operate across an extensive patchwork of highly concentrated markets. Both corporations control vast amounts of wealth and resources, and are able to allocate relatively large amounts of money to potentially harmful practices, such as extensive marketing of unhealthy products. Over recent decades, the proportion of wealth and income transferred by these firms to their shareholders has increased substantially; whereas the proportion of wealth and income redistributed by these two firms to the public via income taxes has considerably decreased. Meanwhile, the distribution of soft drink consumption is becoming increasingly skewed towards population groups in low and middle-income countries (LMICs). Conclusions Market power and corporate wealth and income distribution in the global soft drink market likely compound the market's maldistribution of harms, and indirectly influence health by contributing to social and economic inequalities. Indeed, a 'double burden of maldistribution' pattern can be seen, wherein the wealth of the shareholders of the market's dominant corporations, a group over-represented by a small and wealthy elite, is maximised largely at the expense of the welfare of LMICs and lower socioeconomic groups in high-income countries. If this pattern continues, the appropriate role of the global soft drink market as part of sustainable economic development will require rethinking.